2017
DOI: 10.3389/fphys.2017.00302
|View full text |Cite
|
Sign up to set email alerts
|

4-phenylbutyrate Mitigates Fluoride-Induced Cytotoxicity in ALC Cells

Abstract: Chronic fluoride over-exposure during pre-eruptive enamel development can cause dental fluorosis. Severe dental fluorosis is characterized by porous, soft enamel that is vulnerable to erosion and decay. The prevalence of dental fluorosis among the population in the USA, India and China is increasing. Other than avoiding excessive intake, treatments to prevent dental fluorosis remain unknown. We previously reported that high-dose fluoride induces endoplasmic reticulum (ER) stress and oxidative stress in amelobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Active TGF-β1 may activate and affect organic homeostasis by binding to the transforming growth factor-β receptor 1 (TGF-βR1) through the TGF-β1-Smad signal pathway. Previous studies have shown that fluoride may repress the expression of TGF-β1 (13,41,65,66) and the present study confirmed this result. In the present study, fluoride significantly reduced the expression levels of TGF-β1 in ameloblasts at the gene and protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…Active TGF-β1 may activate and affect organic homeostasis by binding to the transforming growth factor-β receptor 1 (TGF-βR1) through the TGF-β1-Smad signal pathway. Previous studies have shown that fluoride may repress the expression of TGF-β1 (13,41,65,66) and the present study confirmed this result. In the present study, fluoride significantly reduced the expression levels of TGF-β1 in ameloblasts at the gene and protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…Fluoride alters ameloblast function (12), yet the mechanisms associated with DF remain poorly understood despite an increase in DF prevalence (56). Here, we approached the study of DF by analyzing intracellular Ca 2+ signaling and associated effects in enamel cells exposed to fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that 4-PB is anti-apoptotic in stressed ameloblasts is further supported by the report that apoptosis triggered by exposure to fluoride in an ameloblast-derived cell line was inhibited by 4-PB, resulting in an anti-apoptotic BCL2/BAX ratio (Suzuki et al, 2017 ). However, 4-PB was unable to completely prevent fluorosis in mice drinking fluoridated water though it did improve some aspects of the condition compared to control animals who did not receive 4-PB.…”
Section: Targeting Er Stress and The Upr As A Therapeutic Interventiomentioning
confidence: 80%